Evaluasi Pembelajaran Berbasis Proyek pada Materi Magnet, Listrik, dan Teknologi untuk Kehidupan di Kelas 5 SD dengan Model CIPP - Ayu Fadhillah Yunanda; Jesita DMB Damanik; Shanaz Mayla Nissa; Syahrial Syahrial (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to evaluate the effectiveness of project-based learning on Magnetism, Electricity, and Technology for Life material in grade 5 of elementary school using the CIPP (Context, Input, Process, Product) evaluation model. This study uses a quantitative approach with data analysis through SPSS software. Data were collected through questionnaires, observations, and learning outcome tests. The results of the analysis showed that all CIPP components were in the high category, and there was a significant increase in student learning outcomes after the implementation of the project-based learning model.